Prematurity and Neurological Sequelae - Wahed, MA (Bangladesh Journal of Medicine, 2023)
Any birth that takes place three weeks or more before the baby’s due date is a premature birth. Prematurity is a public health problem worldwide. Every year, 15 million infants are born premature, accounting for a prevalence of 11% in 84 surveyed countries. Premature births alone account for a quarter of all neonatal deaths. Survivors of premature births have high rates of postnatal morbidities. With the development technologies and medical procedures, the morbidities are increasing due to improving survival of borderline viable cases. The prevalence of cerebral palsy, intellectual and cognitive dysfunction, retinopathy, hearing loss, epilepsy, ADHD and autistic disorder are more in babies born preterm. The risk of cerebral palsy is 8- 10 times higher in preterm infants and nearly 30 times higher in infants born <32 weeks. Children born preterm have an average 12.9 IQ points lower than term born controls and these children face difficulty in making communication, executive functioning and cognition. ADHD and autism spectrum disorders are frequently diagnosed (OR 3.3) in children born preterm. ROP associated blindness is 10% in high income countries and 40% in middle and low income countries. As many as 10% children born preterm have hearing loss and 35% suffer from different types of epilepsy. Adequate antenatal check-up and immediate postnatal care are key issues to reduce or prevent neurological sequelae in survivors of premature birth. J Medicine 2023; Vol. 34, No. 2(1) Supplement: 212